2006
DOI: 10.1007/s10495-006-6981-2
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of testicular connexins induced apoptosis in rat seminiferous epithelium

Abstract: Spermatogenesis, a tightly regulated developmental process of male germ cells in testis, is associated with temporal and spatial expression of gap junction proteins, such as the connexin family members. Perturbation of their expressions may lead to spermatogenic arrest as manifested by disruption of cell-cell interaction. To explore the role(s) of connexins during spermatogenesis, we utilized the small peptide antagonistic approach to specifically deplete connexin 31, connexin 33, and pan-connexin. Three conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 59 publications
3
68
0
1
Order By: Relevance
“…This hypothesis is in agreement with the previous morphological studies in continual (guinea pig) and seasonal breeder (mink) testes, which suggest that connexin43 (CX43) between SC participates in the formation and regulation of the BTB (Pelletier 1995). Recently, it has been reported that the blockage of CX, by using a pan-CX peptide that recognizes all characterized CX within the testis, concomitantly leads to diminished OCCLUDIN and upregulated N-CADHERIN expression (Lee et al 2006).…”
Section: Sc Btb and Junctional Proteinsmentioning
confidence: 99%
“…This hypothesis is in agreement with the previous morphological studies in continual (guinea pig) and seasonal breeder (mink) testes, which suggest that connexin43 (CX43) between SC participates in the formation and regulation of the BTB (Pelletier 1995). Recently, it has been reported that the blockage of CX, by using a pan-CX peptide that recognizes all characterized CX within the testis, concomitantly leads to diminished OCCLUDIN and upregulated N-CADHERIN expression (Lee et al 2006).…”
Section: Sc Btb and Junctional Proteinsmentioning
confidence: 99%
“…Some authors have found that immature spermatogonia show features of apoptosis, while more mature spermatocytes do not (Allan et al 1987, Russell 1999; however, others have found that in the first wave of spermatogenesis primarily mid-pachytene spermatocytes die by apoptosis (Jahnukainen et al 2004). Cell death is, therefore, a normal process during spermatogenesis, limiting the number of germ cells to ensure that Sertoli cells can provide enough nutrients to nurture the continuous generation of germ cells (Lee et al 2006). The Fas system has been shown to be involved in the regulation of germ cell apoptosis in the rat testis.…”
Section: Introductionmentioning
confidence: 99%
“…When rats were treated with a blocking connexin peptide, disruption of connexin functions using pan-connexin peptide renders the disruption of occludin-based TJ, but not N-cadherin-based AJ in the testes. 23 This proves the vulnerability of the occludin-associated complex following a dysfunction of connexin-based GJ, since pan-connexin peptide with sequence conserved among all connexins virtually blocks all connexin-associated functions in the testes. 23 In addition, the structural association of γ-catenin, an AJ adaptor, and ZO-1, a TJ adaptor, is weakened after treatment of rats using adjudin, which is shown to have a role in disturbing the AJ without compromising the TJ in the testes.…”
Section: Nos/no In Junction Dynamicsmentioning
confidence: 82%
“…23 This proves the vulnerability of the occludin-associated complex following a dysfunction of connexin-based GJ, since pan-connexin peptide with sequence conserved among all connexins virtually blocks all connexin-associated functions in the testes. 23 In addition, the structural association of γ-catenin, an AJ adaptor, and ZO-1, a TJ adaptor, is weakened after treatment of rats using adjudin, which is shown to have a role in disturbing the AJ without compromising the TJ in the testes. 3,24 These findings substantiate the significance of adaptors that mediate cross-talk between different junction types in the testes.…”
Section: Nos/no In Junction Dynamicsmentioning
confidence: 82%
See 1 more Smart Citation